Eksplorasi Kesulitan Pembelajaran Fisika Matematika: Studi Kasus Mahasiswa Tadris Fisika IAIN Kerinci - Siti Riva Darwata; Seprianto; Ismi Adelia (Universitas Garut, 2025)
This research aims to identify and understand the difficulties experienced by students in learning Mathematical Physics at IAIN Kerinci. Based on the results of qualitative data analysis using a case study approach obtained from interviews, classroom observations, and group discussions, it was found that the main factors affecting students' learning difficulties are limitations in basic mathematics mastery, the complexity of physics concepts, and the limitations of interactive teaching strategies. This study recommends the development of more interactive teaching methods, the enhancement of laboratory facilities, and the formulation of a curriculum that prioritizes strengthening the fundamentals of physics and mathematics. The results of this research are also expected to serve as a reference in improving the quality of more adaptive and applicative Mathematical Physics learning according to the academic needs of students.